Effects of Child Protection Policy on the Academic and Behavioral Performance of the Intermediate Learners - Delos Santos, Czelica Lyca (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the extent of the effects of the Child Protection Policy on the behavioral and academic performance of intermediate learners in the Binangonan District, Schools Division Office of Rizal, during the School Year 2025–2026. Utilizing a descriptive research design, the study involved 199 teachers and 370 intermediate learners selected through Slovin’s formula and simple random sampling. Teachers were profiled according to age, sex, civil status, educational attainment, position title, length of service, and in-service trainings attended, while learners were described in terms of sex, sibling position, family size, parents’ educational attainment, occupation, and monthly family income.Findings revealed that teachers perceived the Child Protection Policy as having a “very much effect” on learners’ cognitive, emotional, and social behavior, whereas learners rated its impact as “much effect.” A significant difference was found between teachers’ and learners’ perceptions regarding the policy’s behavioral effects. However, no significant difference was observed when grouped according to teachers’ sex and educational attainment, and learners’ sex, sibling position, family size, father’s educational attainment, parents’ occupation, and family income. Significant differences emerged when teachers were grouped according to age, length of service, civil status, position title, and in-service trainings, and when learners were grouped according to mother’s educational attainment. The learners’ academic performance was rated “Satisfactory,” with a mean grade of 82.11. Moreover, no significant relationship was found between the perceived effects of the Child Protection Policy on behavior and learners’ academic performance.The study concludes that while the policy significantly influences learners’ behavior as perceived by both groups, it does not directly correlate with academic achievement. Recommendations include strengthened monitoring mechanisms, professional development, socio-emotional learning integration, and enhanced parent engagement.